Renewable energy usage for home energy management and its adverse impact due to the increasing trend of electric load addition in homes in the State of Kerala, India - George, Thomas; Selvakumar, A. Immanuel (International Journal of Applied Power Engineering (IJAPE), 2025)
Nowadays renewable energy generation techniques and their application for home energy management are becoming very common topics of discussion all across the globe. The increased user comfort, bill reduction, and government subsidy schemes make more consumers interested in installing these sustainable sources in their homes. Also, the utility company will be able to level its peak load and reduce its carbon footprint. Does installing renewable energy sources in homes with a conventional billing scheme help in reducing the carbon footprint of the utility company? Also, are there chances for an increased trend of electric load addition in homes installed with renewable energy plants having net metering schemes to lead to peak load management burden? This paper is an attempt to underline the benefits of using renewable energy sources at home but at the same time what are the precautions to be taken while using the same in the state of Kerala, India. The paper also proposes an economical portable solar-powered light tower that helps in leveling peak loads in homes with on-grid power plants which are billed under a conventional block rate pricing scheme through net metering.